EVALUASI PENCATATAN DAN PENYAJIAN LAPORAN KEUANGAN BERDASARKAN SAK EMKM PADA UMKM DI KABUPATEN MAJENE - Fatimah Mus, Sari; Amalia Edy, Sri; Amirullah, Sufyan; Mansur, Ahmad (Penerbit Lafadz Jaya, 2025)
This research explores the compliance of Micro, Small, and Medium Enterprises (MSMEs) in Majene Regency with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in their bookkeeping and financial reporting practices. The study's primary focus is to analyze the level of understanding and implementation of these accounting standards among MSME actors. Employing a case study approach, data was collected through questionnaires and in-depth interviews with several MSMEs within the study area. Research findings reveal significant variations in the alignment of MSME accounting practices with SAK EMKM. Some MSMEs have managed their financial records and presented reports reasonably well, although not yet fully adhering to SAK EMKM principles. However, other groups still demonstrate limited understanding and optimal implementation of these standards. These results highlight the urgency of improving financial literacy and accounting capabilities among MSMEs. Therefore, this study recommends intensifying structured training and mentoring programs for MSMEs. The objective is to encourage the preparation of more accurate and transparent financial statements, which in turn will support more strategic business decision-making and the sustainable improvement of MSMEs' financial performance.